Anatomy, Histology, and Ultrastructure of Salivary Glands of the Burrower Bug, Scaptocoris castanea (Hemiptera: Cydnidae). (December 2019) - Cossolin, Jamile Fernanda Silva; Martínez, Luis Carlos; Pereira, Monica Josene Barbosa; Vivan, Lucia Madalena; Bozdoğan, Hakan; Fiaz, Muhammad; Serrão, José Eduardo
Abstract: The burrower bug Scaptocoris castanea Perty, 1830 (Hemiptera: Cydnidae) is an agricultural pest feeding on roots of several crops. The histology and ultrastructure of the salivary glands of S. castanea were described. The salivary system has a pair of principal salivary glands and a pair of accessory salivary glands. The principal salivary gland is bilobed with anterior and posterior lobes joined by a hilus where an excretory duct occurs. The accessory salivary gland is tubular with a narrow lumen that opens into the hilus near the excretory duct, suggesting that its secretion is stored in the lumen of the principal gland. The cytoplasm of the secretory cells is rich in the rough endoplasmic reticulum, secretory vesicles with different electron densities and mitochondria. At the base of the accessory gland epithelium, there were scattered cells that do not reach the gland lumen, with the cytoplasm rich in the rough endoplasmic reticulum, indicating a role in protein production. Data show that principal and accessory salivary glands of S. castanea produce proteinaceous saliva. This is the first morphological description of the S. castanea salivary system that is similar to other Hemiptera Pentatomomorpha, but with occurrence of basal cells in the accessory salivary gland.